Consumer’s perception towards mobile wallet adoption in Malaysia - Chow, Qian Yi (2020)
This paper attempts to delve upon mobile wallet adoption under consumers’ perception in Malaysia context. Technology Acceptance Model has been recruited as base in exploring the relationship of perceived ease of use, perceived usefulness and subjective norm towards the behavioural intention in adopting mobile wallets. A quantitative approach has been used to gather the data via questionnaire. With snowball sampling technique, the data were being accumulated from 168 respondents with varying background and analysed by SPSS. The result proclaimed perceived ease of use, perceived usefulness and subjective norm to have significant positive effect on intention. The output of present study has contributed to fill the potential knowledge gap vastly remain undiscovered, refreshed the existing intention on adoption literature which benefits to mobile payment industry and lift up the awareness of various consumers on mobile wallet existence in such developing nation.